2021
DOI: 10.3389/fmed.2021.757061
|View full text |Cite
|
Sign up to set email alerts
|

Admission Blood Glucose Is Associated With the 30-Days Mortality in Septic Patients: A Retrospective Cohort Study

Abstract: Background: Sepsis, as one of the severe diseases, is frequently observed in critically ill patients, especially concurrent with diabetes. Whether admission blood glucose is associated with the prognosis, and outcome of septic patients is still debatable.Methods: We retrospectively reviewed and analyzed the demographic characteristics of septic patients in the Medical Information Mart for Intensive Care III (MIMIC III, version 1.4) between June 2001 and October 2012. The Chi-square and Fisher's exact tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…22 Other studies in septic inpatients have shown that the mortality increases especially with very low or very high blood glucose levels. 22,31 The presented results are in concordance with earlier studies, showing elevated blood glucose to be associated with increased length of stay in the hospital, in-hospital complications, and mortality in the setting of general surgery. 4 Therefore, the detection of elevated PBG could be taken into account in the prognosis assessment of patients at risk as exemplified by the proposal to include fasting plasma glucose in the prediction of 90-day mortality in viral pneumonia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…22 Other studies in septic inpatients have shown that the mortality increases especially with very low or very high blood glucose levels. 22,31 The presented results are in concordance with earlier studies, showing elevated blood glucose to be associated with increased length of stay in the hospital, in-hospital complications, and mortality in the setting of general surgery. 4 Therefore, the detection of elevated PBG could be taken into account in the prognosis assessment of patients at risk as exemplified by the proposal to include fasting plasma glucose in the prediction of 90-day mortality in viral pneumonia.…”
Section: Discussionsupporting
confidence: 91%
“…As mortality seems to be stable in the present cohort at a PBG range between 140 and 180 mg/dL, a moderate elevation of PBG (<180 mg/dL) may not be as predictive of worse outcomes than higher PBG levels 22 . Other studies in septic inpatients have shown that the mortality increases especially with very low or very high blood glucose levels 22,31 . The presented results are in concordance with earlier studies, showing elevated blood glucose to be associated with increased length of stay in the hospital, in‐hospital complications, and mortality in the setting of general surgery 4 .…”
Section: Discussionsupporting
confidence: 89%
“…Nine studies set a cut-off value for high level blood lactate below 2 mmol/L [33,38,41,85,103,108,124,135,140], while 36 studies recognized the cut-off values for high level blood lactate between 2 and 4 mmol/L [6,11,15,16,34,35,39,43,50,52,53,64- In the pooled analysis, the recommended threshold for identifying the high level of blood lactate varied across the included studies. Nine studies set a cut-off value for high level blood lactate below 2 mmol/L [33,38,41,85,103,108,124,135,140], while 36 studies recognized the cut-off values for high level blood lactate between 2 and 4 mmol/L [6,11,15,16,34,35,39,43,50,52,53,[64][65][66][67][69][70][71][72]76,77,89,94,100,102,106,107,…”
Section: Resultsmentioning
confidence: 99%